Employee Performance Improvement: Compensation and Motivation Sequences - Restu Dwiliansyah; Danya Pamela; Tri Rizky Ardianti; Dadan Hendana; Nabilah Ramadhan (Budapest International Research and Critics University, 2024)
Human Resource Management in Indonesian company is currently under intense scrutiny from various parties. How well human resources are managed will determine the success of the organization in the future. Human resource management will be a very important part of the task of organizational management. PT Adimas Cipta Karya Pratama is one of Telkom's partners, which is engaged in the construction and maintenance of network infrastructure and expected to encourage the growth of broadband access networks in the Greater Bandung area. In addition to the installation of broadband access networks, other services provided are Network Terminal Equipment (NTE), as well as Operations and Maintenance Management Services (O&M - Operation & Maintenance). PT. Adimas Cipta Karya Pratama is required to be able resolving problems related to customer complaints properly, one of them are provide assurance technician that analyze and resolve problem. The higher the level of interruption resolution, the better performance. In the last year, there was a decrease in the realization of performance assurance technician, many factors caused this, but the biggest indication was low motivation and compensation. This research aim to investigate the effect of compensation and motivation to technical assurance performace, using quantitative method and multiple regression as method for hypothesis testing, result shown from 82 respondents taken that simultaneously compensation and motivation have a positive and significant effect on employee performance by 70,2%, but partially, compensation does not affect employee performance, and only motivation that have positive and significant effect on performance.